ТАТМЫН НУГЫН ҮЕТЭН-АЛАГ ӨВСТ БҮЛГЭМДЭЛД ЗОНХИЛОХ ЗАРИМ ЗҮЙЛ УРГАМЛЫН ЦЕНОПОПУЛЯЦИЙН СУДАЛГАА - Нарантуяа, Н; Мөнхзул, О (Proceedings of the Mongolian Academy of Sciences, 2016)
The Hordeum brevisubulatum is indicator of meadow was growing and cover was increased in heavily degraded meadow community due to grazing had been fenced for 4 years is indicating that meadow vegetation has resilience after heavy grazing. As a result of cenopopulation, palatable and high nutrient plants such as Коeleria macrantha, Leymus chinensis, Agrostis Trinii role were decreased in community whereas adults individual with shoots were dominated that is related to the at this phase this kind of plants contains more cellulose thus stem become hard depending on it palatibility is decreased. Therefore fencing of heavily degraded rangeland is main scientific background for proper grazing depending on plant phenology and biology of plants.